Human dimensions of coexistence with elephants in agricultural landscapes in Malaysia - Zahirudin, Natasha Zulaikha (2025)
This thesis explores human-elephant coexistence in Malaysia's agricultural sector, focusing on the palm oil industry. This study employs an interdisciplinary approach that combines the psychological, social and ecological factors of conflicts to investigate the human dimensions of coexistence. The research was conducted across four states in Malaysia and involved 223 questionnaire respondents, 12 focus group discussions, and 75 participants in stakeholder mapping exercises. The questionnaire utilised constructs from The Theory of Planned Behaviour (TPB) and the Norm Activation Model (NAM) to examine the drivers of conflict mitigation intentions and ideas of coexistence. The respondents included executives from the private sector as well as organised and independent smallholders. The findings from Partial Least Squares-Structural Equation modelling (PLS-SEM) reveal that norms towards the government (β=.407, p<.001), negative attitudes (β=-.204, p=.001), and self-efficacy (β=.151, p=.015) significantly explained behavioural intentions (R2= 0.277). Notably, norms towards the government emerged as the strongest predictor, contrary to the findings of previous studies. The extended model incorporating Norm Activation Model constructs improved explanatory power by 12%, with moral obligation, awareness of consequences, and norms towards the government as significant predictors of behavioural intentions (R2= 0.398). The model also investigated the ideas of coexistence through these theories. In the first model, Behavioural intentions (β=.253 p=.004) significantly explained Coexistence ideas (R2=0.065). However, the extended model revealed that awareness of the consequences (β=.337, p<.001) is the strongest predictor variable for coexistence ideas (R2= 0.154). Next, results from reflexive thematic analysis of the focus group discussions with organised smallholders under the Federal Land Development Authority (FELDA) scheme provide a nuanced understanding of the perceived barriers and opportunities for coexistence. Failed mitigation strategies and financial instability owing to crop damage have resulted in prolonged stress and multigenerational debts for settlers. Responses to these conflicts were categorised as "fight”, "flight”, or "freeze”, reflecting accumulated stress from unresolved conflicts. Finally, stakeholder analysis maps key actors within the conflict landscape, revealing their influence, support for coexistence, and potential for collaboration. Non-governmental organizations, village heads, religious leaders, and individuals directly affected by conflict were identified as influential and supportive stakeholders across all four states. The analysis also revealed a trend towards higher influence and support for local-level actors compared to state and federal entities, suggesting the potential benefits of a decentralised approach to conflict management. This thesis proposes reframing human-elephant conflict to coexistence to help shift the focus towards increasing safety for people and elephants, and the exploration of other types of mitigation methods. This emphasises the need for collaboration among intergovernmental agencies, the inclusivity of local stakeholders, and the potential role of sustainability certifications in promoting coexistence strategies. The study's findings suggest that personal moral obligations have a greater influence than governmental pressure on conflict mitigation intentions. This insight, combined with the significant supportive roles of local stakeholders, presents an opportunity to leverage cultural and religious values to promote elephant conservation in agricultural communities. In conclusion, the thesis provides a comprehensive understanding of human-elephant conflicts in Malaysia's agricultural settings, offering insights into the psychological, social, and governance aspects of the issue. It highlights the potential for coexistence based on moral, cultural and religious values while emphasising the need for increased collaboration among various stakeholders to address this complex challenge effectively.